2020
DOI: 10.1177/1758835920951346
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and clinicopathological value of Ki-67 expression in patients with nasopharyngeal carcinoma: a meta-analysis

Abstract: Background: This meta-analysis aimed to identify the prognostic role of Ki-67 in patients with nasopharyngeal carcinoma (NPC). Methods: Relevant studies were retrieved in the PubMed, Embase, Web of Science, and Cochrane Library databases up to November 2019. The pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated to estimate the association between Ki-67 expression and survival outcomes. Combined odds ratios (ORs) and 95% CIs were measured as effect size on the association between Ki-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…KI-67 has been proved to be an prognostic index for multiple solid tumors, for example, high ki-67 expression is closely associated with poor OS and DFS (Disease Free Survival) in lung adenocarcinoma ( 29 ). A meta-analysis including 8 studies showed that high ki-67 expression was associated with poor OS, PFS, and DMFS (distant metastasis-free survival) in patients with nasopharyngeal carcinoma ( 8 ). In hepatocellular carcinoma, high expression of KI-67 has been associated with poor DFS, RFS, and OS ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KI-67 has been proved to be an prognostic index for multiple solid tumors, for example, high ki-67 expression is closely associated with poor OS and DFS (Disease Free Survival) in lung adenocarcinoma ( 29 ). A meta-analysis including 8 studies showed that high ki-67 expression was associated with poor OS, PFS, and DMFS (distant metastasis-free survival) in patients with nasopharyngeal carcinoma ( 8 ). In hepatocellular carcinoma, high expression of KI-67 has been associated with poor DFS, RFS, and OS ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical (IHC) staining is usually used to detect Ki-67, and the expression level of Ki-67 is related to cell proliferation activity, disease progression and cancer recurrence (7). Some studies have shown that Ki-67 is one of the prognostic indices of multiple solid tumors, such as nasopharyngeal carcinoma (8), stage I non-small cell lung cancer (9), gastrointestinal stromal tumour (10), and gliomas (11), resected triple-negative breast cancer (12), colorectal cancer (13), hepatocellular carcinoma (14), and thyroid cancer (15). Previous studies have shown an association between Ki-67 expression and melanoma patient prognosis, but the results have been contradictory (16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…After drawing the ROC curve for blood parameters, we found that monocytes had the best sensitivity and specificity. Two retrospective studies validated age, gender, Ki-67, and smoking and drinking habits as independent prognostic factors for NPC ( 11 , 31 ). Our results showed the model integrating clinical data and the rad-score was more useful than those only using radiomics features.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that a large number of clinical biomarkers such as monocytes (MONO), mean corpuscular volume (MCV), and Ki-67 expression are associated with the tumor microenvironment and tumor immune escape (9)(10)(11). There are no regional differences in the expression of these markers.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between radiomics and clinical symptoms has been widely documented, but other data types, such as genomics, transcriptomics, proteomics, and metabolomics, have been less studied in relation to radiomics. In HNC, correlation studies between imaging and genomics are now available, as important molecular markers such as PD-L1/TP53/ FAT1/KMT2D/NOTCH1/Ki-67 can be predicted by predictive models of imaging features [10,32,141]. At present, the relationship between imaging and transcriptomics has been studied in other tumors, but its combination with proteomics and metabolomics is still less studied.…”
Section: Discussionmentioning
confidence: 99%